THE POTENTIAL AND EFFECTIVENESS OF REGIONAL RETRIBUTIONS INDRAGIRI HULU DISTRICT - Heriasman Heriasman; Suwaji Suwaji; Warnadi Warnadi (LPPM Press STIE Indragiri Rengat, 2021)
This study aims to determine the potential and effectiveness of regional revenue receipts from regional levies in Indragiri Hulu Regency. This study uses a descriptive approach designed to obtain answers to the research objectives. This research data comes from the collection of documents, interviews and data on regional retribution receipts for 2014 – 2020 from the Transportation Agency of Indragiri Hulu Regency. Data analysis is explained by using Potential Analysis, Contribution, Growth Rate and Potential Matrix, and effectiveness ratio. The results of the study show that the potential for regional levies, on average, has the potential to be developed, but in terms of management and implementation effectiveness, it is still not optimal. Based on quantitative data analysis, parking fees are categorized as potential with positive growth, motor vehicle testing fees have good growth opportunities and have the potential to be developed, while terminal fees and route permit fees are underdeveloped categories. Based on the effectiveness ratio analysis, parking fees are categorized as very effective, motor vehicle testing fees are included in the fairly effective criteria, terminal fees are quite effective, and route permit fees are categorized as quite effective.